PERFOMANCE MEASUREMENT MODEL OF URBAN AREA PLAN WITH LIVABILITY APPROACH (CASE STUDY: CIBEUNYING AREA, BANDUNG CITY) - Kusuma Triwardana, Audia
Good planning and design are important in realizing a quality of life (livable) impact on all aspects of life, such as being able to walk. This good plan and design are what can create a livable and sustainable space. Until now the existing measurements are limited to the habitability index not based on spatial urban areas and the green neighborhood measurements from GBCI are limited to an area of 60 ha. Thus, the need for a model that can measure an urban area plan with a livability approach to be able to determine the level of livability of an urban area which can be poured into a more detailed plan later and can provide benefits to stakeholders in making decisions for further development and monitoring of the city as well as in assessing the city's plan towards livability.